Application of the Flipped Classroom Model Using Games-Based Learning Multimedia in Increasing Students’ Learning Outcomes - Bayu Pradikto; Sofino (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
This paper discusses the low students’ learning outcomes and declining student satisfaction in non-formal education learning technology courses, where both distance and face-to-face learning are limited. This study aimed to improve learning outcomes in the Non-Formal Education Learning Technology course of the S1 Non-Formal Education Study Program through the implementation of game-based learning multimedia combined with the flipped classroom model. The research was conducted on 30 students of semester III/A using a Pre-Experimental Design with a One-Group Pretest–Posttest Design. The flipped classroom model was applied both in the classroom and at students’ homes. Data collection was carried out through testing, consisting of a pretest to measure students’ initial abilities and a posttest to examine the effect of the treatment. Data analysis employed three statistical tests, namely normality, homogeneity, and hypothesis testing. The results showed that the sample data were normally distributed and homogeneous after treatment. Hypothesis testing revealed a significant effect of game-based multimedia flipped classroom implementation on learning outcomes in the non-formal education learning technology course, with the experimental class achieving an average score of 81.63.